ICT4D evaluation: its foci, challenges, gaps, limitations, and possible approaches for improvement. Issue 2 (3rd April 2022) - Yim, Moonjung; Gomez, Ricardo
ABSTRACT: With significant cases of failures in information and communication technologies for development (ICT4D or ICTD), much attention has been paid to the importance of evaluation to improve project sustainability. Using the Capability Approach and human development notion as a theoretical lens, this study examines the foci of the ICT4D evaluation, its challenges and gaps, and possible approaches to address the challenges and gaps. The study conducted content analyses of 108 peer-reviewed journal articles and 114 aid/development agency reports, and interviews with 24 researchers in the academic and practitioner spheres. The study finds that the foci of the ICT4D evaluation can be described in terms of areas such as continental/regional focus, method and research design, notion of development, and evaluation focus. Moreover, the study finds that challenges exist surrounding impact assessment, which can be addressed by clarifying the development notion–impact connection in the evaluation process and focusing on the evaluation capacity building (ECB) of project participants. In addition, the study highlights the importance of the domain-based approach in the ICT4D evaluation.